Tradisi Baritan Pada Hari Jumat Kliwon Di Desa Sendangdawuhan Kendal Jawa Tengah - Restin Trisna Utami; Atiqa Sabardila (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
Baritan is one in every of many agricultural cultural societies which have been cultivated thru the ages, together with the Baritan subculture cultivated through the human beings of Sendangdawuhan village in Kendal. The Baritan lifestyle is a part of the day by day habitual practiced yearly through the Sendangdawuhan network as a shape of gratitude to God for offering wealth thru bountiful harvests in order that the human beings can meet their day by day needs. Carrying changed into understood from the Baritan lifestyle. Baritan carried out through the human beings of Sendangdawuhan village has a couple of cost advantages, together with sociological cost, specifically the lifestyles of those sports that join social connections of various corporations of human beings.